RESIKO KEHAMILAN PADA USIA REMAJA - ., Wijayanti (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Pregnancy is with child (gestation of previous menstrual period until delivery, which normally is 40 weeks or 280 days ) and divided into three periods, or trimesters each lasting three months ( brooken, 2008: 265) . Conditions pregnancy can be divided into two categories, namely women with normal pregnancies and pregnancies with high risk. A pregnant woman diketegorikan as a high risk group if pregnancy is not desired / desirable; women experience complications during pregnancy such as bleeding , preterm birth, and fetal anomalies diagnosed conginetal , depression , domestic violence and the mother had a previous history of high risk pregnancies (Trask, 2011). High risk of teenage pregnancy experienced by mothers include: miscarriage, bleeding, infection, anemia, pregnancy, pregnancy poisoning ( gestosis ), which is a long and difficult labor . Risks for the baby include: prematurity, low birth weight (LBW), birth defects, infant mortality. Keywords : pregnancy , teen